KONTROL DIRI TERHADAP PERILAKU KONSUMEN - Larasati, Dewi (Universitas Islam Syekh Yusuf, 2023)
The current study analyzes Fruits and Vegetables on Consumption Behavior. This research was conducted using a descriptive quantitative approach method. The results of this research analysis show a high level of awareness among SMA/SMK/MA teenagers regarding the importance of vegetables and fruit in everyday life. Consuming fruit and vegetables can provide benefits for teenagers' health in the future, such as controlling body weight or obesity, as well as preventing the risk of various diseases. Lack of consumption of vegetables and fruit among teenagers causes health problems in the body.